PENETAPAN KADAR TANIN PADA KULIT PISANG RAJA (Musa sapientum) DENGAN METODE PERMANGANOMETRI - Mariani Tarigan (LP2MTBM MAKARIOZ, 2018)
Macroscopic and microscopic tests showed that the samples taken were true of plantain skin (Musa sapientum). The identification of tannin compounds in plantain skin using FeCl3 gave a blue-black color indicating tannins. The tannin content contained in the skin of plantain (Musa sapientum) was 1.7% which was carried out by the permanganometry method